PHYSICAL EDUCATION SCHOOL: IN SEARCH ENGINE DEVELOPMENT (Fiep Bulletin - online, 2012)
This study aimed to evaluate the motor performance of children of six and seven years old For this purpose, we analyzed 30 children, 15 boys and 15 girls, 6 and 7 years old studying in a private network of Mogi das Cruzes. The children were submitted to the Test of Gross Motor Development (TGMD), the teacher participated in a semi-structured interviews that were designed to investigate the contents, objectives and methods worked out in class, as well as the main motor difficulties of the subjects of this study. The data were presented by descriptive analysis and values of central tendency (mean) and dispersion (standard deviation), suffering a first test of normality Shapiro-wilking. For data that showed a normal distribution we used the Student's t test for independent samples to compare the groups, and those with a non-normal distribution Kruman Wallis test. All tests were performed in the computer package SPSS 19.0 for Windows, with the significance level of p
Keywords: motor development; physical education; motor delays